How Do Banks' Funding Costs Affect Interest Margins? - Arvid Raknerud; Bjørn Helge Vatne; Ketil Johan Rakkestad (Norges Bank, 2011)
We use a dynamic factor model and a detailed panel data set with quarterly accounts data on all Norwegian banks to study the effects of banks' funding costs on their retail rates. Banks' funds are categorized into two groups: customer deposits and long-term wholesale funding (market funding from private and institutional investors including other banks). The cost of market funding is represented in the model by the three-month Norwegian Inter Bank Offered Rate (NIBOR) and the spread of unsecured senior bonds issued by Norwegian banks. Our estimates show clear evidence of incomplete pass-through: a unit increase in NIBOR leads to an approximately 0.8 increase in bank rates. On the other hand, the difference between banks' loan and deposit rates is independent of NIBOR. Our findings are consistent with the view that banks face a downward-sloping demand curve for loans and an upward-sloping supply curve for customer deposits.
hdl:11250/2496953
Keywords: E43; E27; C33; 330; NIBOR; norwegian inter bank offered rate; interest rates; pass-through; funding costs; bank panel data; dynamic factor model